Self-fulfilling prophecy and the future of doping - Moston, S.; Engelberg, T.; Skinner, J. (Psychology of Sport and Exercise, 2015)
Objectives: Surveys of the perceived incidence of doping in sport suggest that such behaviour is relatively common. Perceptions may potentially be of greater significance than actual incidence: athletes who believe that other athletes are doping may be more likely to engage in such practices, potentially creating a damaging self-fulfilling prophecy. Design: A cross-sectional study examines the effects of age (range 12-17 years), gender and involvement in sport (elite athletes and non-athletes) on the perceived incidence of doping. A measure of moral functioning was included as a covariate. Methods: 312 participants were asked to estimate the incidence of doping in elite sport, to name a sport they believed in which doping was most prevalent, and to complete a short survey assessing level of moral functioning and demographic characteristics. Results: The overall estimated incidence of doping was 28.8%, with athletics, weightlifting and cycling named as the sports in which doping was perceived to be most prevalent. Perceived incidence data were analysed using a 3 (age group: 12-13, 14-15, 16-17) × 2 (gender) × 2 involvement in elite sport (non-athletes, elite athletes) ANACOVA, with the covariate of moral functioning. There were significant effects of both age group and gender on estimates of doping. Involvement in sport was not linked to perceived incidence. There was a significant (negative) relationship between moral functioning and estimates of doping. Conclusions: Findings are discussed in relation to the potential diffusion of doping behaviours and the content of anti-doping initiatives, such as attempting to counter doping through teaching the `morality of sport`.